2023
DOI: 10.1093/tbm/ibac089
|View full text |Cite
|
Sign up to set email alerts
|

Shift patterns, physical exercise, and Type 2 diabetes mellitus (T2DM): a prospective cohort study in China

Abstract: To examine the relationships between different shift patterns and Type 2 diabetes mellitus (T2DM) risk, and determine whether physical exercise reduced the incidence of T2DM in shift workers in the oil industry. Baseline data were collected from participants in May 2013 who were then followed for 4 years in a prospective cohort study. The cohort initially consisted of 3,002 workers and ultimately included 2,827 people. Baseline and follow-up questionnaires were sent to participants every 2 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Variations in both the secretion and sensitivity of insulin display obvious circadian rhythms, and glucose tolerance (GT) is higher in the morning than in the evening in healthy people, but this oscillation disappears in T2D patients and IGT appears when the circadian oscillation is damaged ( 72 74 ). Many studies have revealed that the risk of IR and T2D is higher in populations with sleep disorders, SJL, and shift work, and it may be reduced by extended sleep duration and circadian readjustment strategies ( 11 , 75 ). Cui et al.…”
Section: Association Between Circadian Rhythm Disturbance and Ksdmentioning
confidence: 99%
“…Variations in both the secretion and sensitivity of insulin display obvious circadian rhythms, and glucose tolerance (GT) is higher in the morning than in the evening in healthy people, but this oscillation disappears in T2D patients and IGT appears when the circadian oscillation is damaged ( 72 74 ). Many studies have revealed that the risk of IR and T2D is higher in populations with sleep disorders, SJL, and shift work, and it may be reduced by extended sleep duration and circadian readjustment strategies ( 11 , 75 ). Cui et al.…”
Section: Association Between Circadian Rhythm Disturbance and Ksdmentioning
confidence: 99%
“…As a rising health burden, the number of adults living with diabetes was estimated to reach 537 million in 2021, corresponding to 10.5% of the world population. Although the epidemiological association between circadian rhythm and T2DM has been reported [ 9 , 10 ], the underlying mechanisms are complex and remain unclear. Melatonin and its receptors serve as intermediaries in synchronizing human endogenous circadian rhythm with environmental rhythms [ 11 ].…”
Section: Introductionmentioning
confidence: 99%